Phylogenetic position of Vanda coelestis (Rchb.f.) Motes (Orchidaceae; Aeridinae): evidence from complete plastome and combined traditional sequences - Zeng, Meng-Yao; Chen, Jin-Liao; Huang, Ming-Zhong; Li, Ming-He (Phytotaxa, 2024)
The taxonomic status of Vanda coelestis (Rchb.f.) Motes remains a matter of discussion. So far, molecular systematic work has not been used to investigate. Here, we conducted the phylogenetic analyses using two datasets, the complete plastome and a combination of traditional molecular sequences (nrITS, matK, psbA-trnH, and trnL-trnF). Plastid-based phylogenetic trees indicated that this species was deeply embedded within the genus Vanda. In the analysis based on combined traditional sequences dataset, this species was further supported as sister to V. vietnamica with strong support.